Life cycle of Leptaulax koreanus (Nomura, Kon, Johki, & Lee) (Coleoptera: Passalidae): A Korean endemic species - Seung Jin Roh (Elsevier, 2021)
Leptaulax koreanus is an endemic species inhabiting the Gwagneung Forest in Pocheon-si, Gyeonggi-do, Korea. However, its developmental characteristics have not been well studied. Thus, the aim of this study was to establish data on the developmental characteristics of L. koreanus via indoor rearing. Developmental characteristics were examined under indoor conditions (25°C, 70% relative humidity, 16L:8D), where females oviposited between 12 and 63 eggs (32 eggs on average) during the ovipositing season and with the highest ovipositing rate on the 21st day after the first oviposition. Immediately after ovipositing, the eggs were reddish brown in color, changing to green upon maturation. The durations of each developmental stages were 9.8 ± 2.2 d, 8.6 ± 1.4 d, 15.6 ± 2.4 d, and 7.2 ± 1.8 d for the first instar, second instar, third instar, and pupation, respectively, with the lifespan of the adults found to be greater than 1 year. The results in this study would be a useful source of information for the mass rearing conservation of L. koreanus.